LO39: Healthcare costs among homeless and/or substance using adults presenting to the emergency department: a single centre study. (15th May 2017) - Puri, V.V.; Dong, K.; Rowe, B.H.; Kirkland, S.W.; Vandenberghe, C.; Salvalaggio, G.; Cooper, R.; Newton, A.; Wild, C.; Gupta, S.; Khangura, J.K.; Villa-Roel, C.; et al.
Abstract : Introduction: Active substance use and unstable housing are both associated with increased emergency department (ED) utilization. This study examined ED health care costs among a cohort of substance using and/or homeless adults following an index ED visit, relative to a control ED population.Methods: Consecutive patients presenting to an inner-city ED between August 2010 and November 2011 who reported unstable housing and/or who had a chief presenting complaint related to acute or chronic substance use were evaluated. Controls were enrolled in a 1:4 ratio. Participants' health care utilization was tracked via electronic medical record for six months after the index ED visit. Costing data across all EDs in the region was obtained from Alberta Health Services and calculated to include physician billing and the cost of an ED visit excluding investigations. The cost impact of ED utilization was estimated by multiplying the derived ED cost per visit by the median number of visits with interquartile ranges (IQR) for each group during follow up. Proportions were compared using non-parametric tests.Results: From 4679 patients screened, 209 patients were enrolled (41 controls, 46 substance using, 91 unstably housed, 31 both unstably housed and substance using (UHS)). Median costs (IQR) per group over the six-month period were $0 ($0-$345.42) for control, $345.42 ($0-$1139.89) for substance using, $345.42 ($0-$1381.68) for unstably housed and $1381.68 ($690.84-$4248.67) for unstably housed and substance using patients (p<0.05).Conclusion: The intensity of excess ED costs was greatest in patients who were both unstably housed and presenting with a chief complaint related to substance use. This group had a significantly larger impact on health care expenditure relative to ED users who were not unstably housed or who presented with a substance use related complaint. Further research into how care or connection to community resources in the ED can reduce these costs is warranted.